Pengaruh Konservatisme Akuntansi, Struktur Modal, Investment Oportunity Set (IOS) Terhadap Kualitas Laba - Mashita Suryani; Suwarno Suwarno (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Organizations positively need great benefit quality to draw in financial backers and partners. Quality benefits can give quality data and decrease insight unsettling influences, so they can give a precise evaluation of organization execution. A few variables can impact profit quality, including bookkeeping traditionalism, capital construction, and speculation opportunity sets. Subsequently, this exploration means to audit whether these variables impact income quality. This exploration technique utilizes a quantitative methodology including 4 insurance agency, 15 non-bank monetary organizations, and 35 financial organizations. Of the 35 financial organizations, 25 of them recorded positive benefits for four back to back years. 25 businesses were the total number of samples observed over the course of a year. In this way, the all out perception information gathered more than four years is 100. The information got was broke down with a few tests utilizing SPSS. The exploration results show that bookkeeping traditionalism variables can reinforce profit quality. Capital construction factors play a part in adjusting hazard and return. The quality of earnings data can be improved by using the investment opportunity set factor. In light of the outcomes, it is presumed that bookkeeping traditionalism, capital design and the assortment of venture open doors affect profit quality. Keywords: Earnings quality, Accounting conservatism, Capital structure, Investment opportunity set